Including women's empowerment as a key component of the United States’ global initiative to combat hunger – Role of the Women's Empowerment in Agriculture Index - CGIAR Research Program on Policies, Institutions, and Markets (2018)
Findings using the Women's Empowerment in Agriculture Index helped the United States Government target key areas of women’s disempowerment in the design of Feed the Future country programs, and informed the United States Global Food Security Strategy Country Plans for Bangladesh, Ethiopia, Honduras, Kenya, and Nigeria.